The Oxford handbook of religion and Europe - Davie, Grace 1946-; Leuştean, Lucian 1967- (Oxford New York, NY Oxford University Press, 2022)
This authoritative collection offers a detailed overview of religious ideas, structures, and institutions in the making of Europe. Written by leading scholars in the field, it demonstrates the enduring presence of lived and institutionalised religion in the social networks of identity, policy, and power over two millennia of European history.
Also issued in print: 2021. - Includes bibliographical references and index. - Description based on online resource; title from home page (viewed on December 6, 2021)
Keywords: Church and state -- History -- Europe; Religion and civil society -- History -- Europe; Church and state; Religion; Religion and civil society; Religion and state; History; Europe -- Church history; Europe; Aufsatzsammlung